2018
DOI: 10.1055/a-0591-9054
|View full text |Cite
|
Sign up to set email alerts
|

Role of video capsule endoscopy in patients with constitutional mismatch repair deficiency (CMMRD) syndrome: report from the International CMMRD Consortium

Abstract: Background and study aims  Constitutional mismatch repair deficiency (CMMRD) syndrome, also known as biallelic mismatch repair deficiency (BMMRD) syndrome is a rare autosomal-recessive genetic disorder that has a high mortality due to malignancy in childhood and early adulthood. The small bowel phenotype in CMMRD is not well described and surveillance protocols for small bowel cancer have not been well established. This study was conducted to evaluate the usefulness and clinical impact of video capsule endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…In addition, benign duodenal lesions were detected and removed endoscopically in 27% of our patients. In the recent Consortium studies, no cancers of oesophagus or stomach were reported 9 10. We are not able to make conclusions on the value of VCE in the present study because in only 2 of 10 patients who underwent this procedure small polyps were detected and 1 patient developed a symptomatic SBC outside the programme.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…In addition, benign duodenal lesions were detected and removed endoscopically in 27% of our patients. In the recent Consortium studies, no cancers of oesophagus or stomach were reported 9 10. We are not able to make conclusions on the value of VCE in the present study because in only 2 of 10 patients who underwent this procedure small polyps were detected and 1 patient developed a symptomatic SBC outside the programme.…”
Section: Discussioncontrasting
confidence: 61%
“…The investigators concluded that although VCE was found to be effective to detect neoplasia of the small intestine, incomplete studies in 28%, false negative and positive results were found to be limiting factors of this screening modality. 10 Colonoscopic surveillance in our cohort led to the detection and removal of many adenomas including adenomas with highgrade dysplasia. One early asymptomatic CRC as well as one advanced CRC were found.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations